The design and performance of a 2.5-GHz telecommand link for wireless biomedical monitoring. - Crumley, G.C.
This paper details the implementation and operational performance of a minimum-power 2.45-GHz pulse receiver and a companion on-off keyed transmitter for use in a semi-active, duplex RF biomedical transponder. A 50-Ω microstrip stub-matched zero-bias diode detector forms the heart of a body-worn receiver that has a CMOS baseband amplifier consuming 20 μA from +3 V and achieves a tangential sensitivity of -53 dBm. The base transmitter generates 0.5 W of peak RF output power into 50 Ω. Both linear and right-hand circularly polarized Tx-Rx antenna sets were employed in system reliability trials carried out in a hospital coronary care unit. For transmitting antenna heights between 0.3 and 2.2 m above floor level, transponder interrogations were 95% reliable within the 67-m 2 area of the ward, falling to an average of 46% in the surrounding rooms and corridors. Overall, the circular antenna set gave the higher reliability and lower propagation power decay index.
Keywords: 0.5 W; 2.5 GHz; 20 muA; 3 V; 50 ohm; CMOS baseband amplifier; UHF; Body-worn receiver; Circular antenna set; Corridors; Duplex RF biomedical transponder; Hospital coronary care unit; Linear circularly polarized antenna; Microstrip stub-matched diode detector; On-off keyed transmitter; Peak RF output power; Propagation power decay index; Pulse receiver; Right-hand circularly polarized antenna; Rooms; Semi-active transponder; System reliability trials; Tangential sensitivity; Telecommand link design; Telecommand link performance; Transmitting antenna heights; Transmitting-receiving antenna; Wireless biomedical monitoring